2007
DOI: 10.1124/mol.107.038836
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Action Mechanisms of Toxic Chemicals Using JFCR39, a Panel of Human Cancer Cell Lines

Abstract: We previously established a panel of human cancer cell lines, JFCR39, coupled to an anticancer drug activity database; this panel is comparable with the NCI60 panel developed by the National Cancer Institute. The JFCR39 system can be used to predict the molecular targets or evaluate the action mechanisms of the test compounds by comparing their cell growth inhibition profiles (i.e., fingerprints) with those of the standard anticancer drugs using the COMPARE program. In this study, we used this drug activity da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…system, an informatic anticancer drug discovery system for molecular target identification JFCR39 is an informatic anticancer drug screening system we established in the early 1990s by utilizing a human cancer cell line panel JFCR39 coupled with a drug-activity database [1][2][3][4] . This system was developed based on the NCI60 system [5] with some modifications [4] .…”
Section: Jfcr39 (Japanese Foundation For Cancermentioning
confidence: 99%
“…system, an informatic anticancer drug discovery system for molecular target identification JFCR39 is an informatic anticancer drug screening system we established in the early 1990s by utilizing a human cancer cell line panel JFCR39 coupled with a drug-activity database [1][2][3][4] . This system was developed based on the NCI60 system [5] with some modifications [4] .…”
Section: Jfcr39 (Japanese Foundation For Cancermentioning
confidence: 99%
“…18) ZSTK474 is a novel PI3K inhibitor, identified in our laboratory by COMPARE analysis using a panel of 39 human cancer cell lines coupled to a drug-activity database. [19][20][21][22][23] ZSTK474 exhibited highly promising antitumor efficacy without observable toxicity. We previously reported that ZSTK474 inhibited all four PI3K isoforms, indicative of a pan-PI3K inhibitor, while retaining high selectivity for PI3K over 140 protein kinases.…”
mentioning
confidence: 99%
“…The white powder was corrected on funnel, which was thoroughly washed with CH 3 CN and MeOH to give pure sample of 22 (14.9 Cells and Reagents Human lung cancer cell line A549 was obtained as described. 22) NHLF normal human lung fibroblasts were obtained from BioWhittaker. The stromal cells were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 100 units/mL penicillin G, 100 µg/mL streptomycin, ITH (5 µg/ mL insulin, 5 µg/mL transferrin, and 1.4 µM hydrocortisone), and 5 ng/mL basic-FGF (Pepro Tech, NJ, U.S.A.) at 37°C with 5% CO 2 as described. )…”
Section: Methyl (S)-2-((s)-2-((((9h-fluoren-9-yl)methoxy)carbonyl)amimentioning
confidence: 99%